Interleukin-4-Enhanced Oligodendrocyte Differentiation Depends on Extracellular Zinc Uptake via ZIP11 - Aratake, Takaaki; Kurita, Serika; Wegner, Michael (Cells, 2025)
Differentiation of oligodendrocytes and myelination are enhanced by interleukin-4, an anti-inflammatory cytokine secreted from immune cells or injured neurons, and peroxisome proliferator-activated receptor γ serves as a central effector. While intracellular zinc concentrations have recently been reported to change dynamically during oligodendrocyte development, the role of zinc in interleukin-4-enhanced oligodendrocyte differentiation has not been studied. Using primary oligodendroglial cells and the oligodendroglial CG4 cell line, we show that intracellular zinc concentrations transiently increased 1 day after interleukin-4-induced differentiation and that intracellular as well as extracellular zinc chelators repressed the interleukin-4-dependent effects. Our analyses furthermore reveal that STAT6 activated the zinc transporter ZIP11 downstream of interleukin-4 in a phosphorylation-dependent manner and that siRNA-dependent knockdown of ZIP11 abolished the interleukin-4-enhanced oligodendrocyte differentiation. An antagonist of peroxisome proliferator-activated receptor γ similarly repressed the interleukin-4-dependent differentiation. However, agonists did not affect intracellular zinc concentrations. These findings indicate that interleukin-4 upregulates ZIP11 expression via activation of STAT6 and facilitates extracellular zinc uptake, which in turn activates peroxisome proliferator-activated receptor γ and thereby promotes oligodendrocytes differentiation. Our results argue that a modulation of zinc concentrations may be beneficial for promoting oligodendrocyte differentiation and remyelination under demyelinating conditions such as multiple sclerosis.
CRIS-Team Scopus Importer:2025-12-05
Keywords: glia; IL-4; oligodendrocyte; zinc; zinc transporter; ZIP11